Testing of the Indonesian Version of the Instrument “Teachers’ Sense of Efficacy Scale” Using Rasch Modelling [Pengujian Kualitas Instrumen Teachers’ Sense of Efficacy Scale Versi Bahasa Indonesia Menggunakan Pemodelan Rasch] - Herdiyan Maulana; Anna Armeini Rangkuti; Bambang Sumintono; Lussy Dwi Utami (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2020)
Teachers who have self-efficacy regarding their abilities play an important part in the educational process. The instrument “Teachers’ Sense of Efficacy Scale (TSES)”, which consists of 24 items, measures the self-efficacy of a teacher in conducting his or her role in the classroom. This research was aimed at testing the psychometric properties of the Indonesian language version of the TSES, using Rasch testing. 245 State Primary School teachers in the Special Capital District (Daerah Khusus Ibukota - DKI) of Jakarta, Indonesia, took part in the study. Analysis results indicated that the reliability index and the separation of item and person scales of the TSES fulfil the criteria well. In the study of the structure of the organisation of the instrument, tests of the unidimensional quality and accuracy of the items/models showed they fulfil the conditions for measurement by Rasch modelling. In the rating scale, data analysis indicated the necessity of simplification of the range of response choices, and also of the variation in the difficulty of the items, which is not very uniform, so that a large proportion of respondents were not easily measurable, via this instrument. The results of the research indicated two items which showed bias, when dealt with by different groups of respondents. Based upon the information resulting from this testing, this script discusses recommendations for the modification of the Indonesian language version of the TSES instrument, with the aim of producing an instrument having good psychometric qualities, to measure the self-efficacy of teachers. Guru yang mempunyai efikasi diri akan kemampuannya merupakan bagian penting dalam proses pendidikan. Instrumen Teachers’ Sense of Efficacy Scale (TSES), yang berisi 24 butir, mengukur efikasi diri seorang guru dalam menjalankan perannya di kelas. Penelitian ini bertujuan untuk menguji properti psikometrik TSES versi Bahasa Indonesia dengan menggunakan pemodelan Rasch. Sebanyak 245 orang guru SD Negeri di DKI Jakarta berpartisipasi dalam studi ini. Hasil analisis menunjukkan indeks reliabilitas serta separasi item dan person skala TSES memenuhi kriteria yang baik. Dalam kajian struktur penyusun instrumen, uji unidimensionalitas dan ketepatan butir-model memenuhi syarat dalam pengukuran pemodelan Rasch. Dalam hal skala peringkat (rating scale), analisis data menunjukkan perlunya penyederhanaan rentang pilihan jawaban; juga variasi tingkat kesulitan butir yang tidak terlalu beragam sehingga sebagian besar responden tidak dapat terukur dengan baik melalui instrumen ini. Hasil penelitian ini menunjukan dua butir yang memiliki bias ketika di kerjakan oleh kelompok responden yang berbeda. Berdasarkan informasi hasil pengujian tersebut, tulisan ini membahas usulan modifikasi instrumen TSES versi Bahasa Indonesia dengan tujuan menghasilkan instrumen efikasi diri guru yang memiliki properti psikometrik yang baik.